An investigation of the substitution rate and environmental impact associated with secondhand clothing consumption in the United States - Patwary, Sarif Ullah (Kansas State University, 2020)
Due to massive environmental pollution and resource depletion associated with post-consumer clothing waste, secondhand clothing (SHC) consumption is recognized as one of the critical sustainable strategies. However, the environmental benefit of clothing reuse has not been studied rigorously. Moreover, one of the main factors of assessing the environmental benefit of reuse, termed as substitution rate (SR), is also an understudied topic. The SR attempts to estimate how much new clothing is not purchased as a result of a secondhand purchase. This study identified the SR value of SHC consumption for U.S. consumers and examined the influence of various factors associated with it. Using the SR value, the study also assessed the potential environmental benefit of secondhand use of a 100% cotton knit t-shirt. An online questionnaire survey was administered to 920 U.S. participants who purchased SHC items in the past year. The SR value was calculated using collected data, and a one-sample t-test was used to examine the difference of SR between U.S. consumers and other reported European and African countries in the published studies. A cluster analysis was conducted to explore the typologies of U.S. participants based on their age, gender, race, household income, motivation/barrier of purchasing SHC, and SR value. Besides, Poisson regression analysis was conducted to investigate if/how age, gender, race, household income, and motivation/barrier of purchasing SHC predict SR value. Finally, life cycle assessment (LCA), typically a ‘cradle-to-grave’ approach of identifying the environmental impact of a product, process, or service in various stages of the corresponding life cycle, of secondhand use of a 100% cotton knit men’s t-shirt was conducted to assess the environmental benefit of clothing reuse. The result indicated that the average SR of various secondhand clothing types for U.S. participants was 67.81% ± 4.96. This finding suggests that, on average, 100 SHC purchases substitutes between about 63 and 73 new purchases. It was found that the SR value of U.S. participants was significantly higher (M = 67.81, SD = 8.45) than the average 45.13 SR value for other selected European and African countries. Female participants showed lower SR than male participants, and the difference of substitution rate across different gender groups was statistically significant (F [2, 890] = 3.23, p < .05). Similarly, younger participants showed higher SR than older participants. Furthermore, this study also found that higher income was associated with a higher SR value. However, age, gender, race, household income, motivation, and barrier were not good predictors of SR value in the regression model. The finding further indicated that the secondhand use of a 100% cotton men’s t-shirt resulted in a potential saving of an estimated 1.48 kg CO2 eq. GHG emission, 1.8 m3 water consumption, and 1.06 m2a eq. land use, considering 56.7% SR value for the t-shirt. This study filled an important data gap as related to the SR value of SHC, especially for U.S. consumers. This study also made an initial attempt to understand the potential environmental impact of SHC consumption in the context of the United States. The study would provide SHC-based brands and retailers with an estimation of the potential environmental benefit of SHC, thereby offering a likely marketing opportunity. Overall, this study lends strong support to the existing body of knowledge that clothing reuse is better than disposing of clothes, and the potential environmental benefit can still be realized with as low as 5% SR value.
Keywords: Clothing; Textiles; Apparel; Substitution rate; Sustainability; Life cycle assessment (LCA)